Prepartum dietary energy intake alters adipose tissue transcriptome profiles during the periparturient period in Holstein dairy cows - Minuti, Andrea (J Anim Sci Biotechnol, 2020)
BACKGROUND: The aim of the study was to investigate the effect of energy overfeeding during the dry period on adipose tissue transcriptome profiles during the periparturient period in dairy cows. METHODS: Fourteen primiparous Holstein cows from a larger cohort receiving a higher-energy diet (1.62 Mcal of net energy for lactation/kg of dry matter; 15% crude protein) for ad libitum intake to supply 150% (OVR) or 100% (CTR) of energy requirements from dry off until parturition were used. After calving, all cows received the same lactation diet. Subcutaneous adipose tissue (SAT) biopsies were collected at − 14, 1, and 14 d from parturition (d) and used for transcriptome profiling using a bovine oligonucleotide microarray. Data mining of differentially expressed genes (DEG) between treatments and due to sampling time was performed using the Dynamic Impact Approach (DIA) and Ingenuity Pathway Analysis (IPA). RESULTS: There was a strong effect of over-feeding energy on DEG with 2434 (False discovery rate-corrected P < 0.05) between OVR and CTR at − 14 d, and only 340 and 538 at 1 and 14 d. The most-impacted and activated pathways in the Kyoto Encyclopedia of Genes and Genomes (KEGG) database that were highlighted by DIA analysis at − 14 d in OVR vs. CTR included 9 associated with carbohydrate metabolism, with ‘Pyruvate metabolism’, ‘Glycolysis/gluconeogenesis’, and ‘Pentose phosphate pathway’ among the most-activated. Not surprisingly, OVR led to marked activation of lipid metabolism (e.g. ‘Fatty acid biosynthesis’ and ‘Glycerolipid metabolism’). Unexpected metabolic pathways that were activated at − 14 d in OVR included several related to metabolism of amino acids (e.g. branched chain) and of cofactors and vitamins (thiamin). Among endocrine and immune system pathways, at − 14 d OVR led to marked activation of ‘PPAR signalling’ and ‘Antigen processing and presentation’. Among key pathways affected over time in OVR, a number were related to translation (e.g. mTOR signaling), endocrine/immune signaling (CXCR4 and IGF1), and lipid metabolism (oxidative phosphorylation) with greater activation in OVR vs. CTR specifically at − 14 d. Although statistical differences for several pathways in OVR vs. CTR nearly disappeared at 1 and 14 vs. − 14 d, despite the well-known catabolic state of adipose depots after calving, the bioinformatics analyses suggested important roles for a number of signaling mechanisms at − 14 vs. 14 than 1 vs. -14 d. This was particularly evident in cows fed to meet predicted energy requirements during the dry period (CTR). CONCLUSIONS: Data underscored a strong activation by overfeeding energy of anabolic processes in the SAT exclusively prepartum. The study confirmed that higher-energy diets prepartum drive a transcriptional cascade of events orchestrated in part by the activation of PPARγ that regulate preadipocyte differentiation and lipid storage in SAT. Novel aspects of SAT biology to energy overfeeding or change in physiologic state also were uncovered, including the role of amino acid metabolism, mTOR signaling, and the immune system.